Relative total phenolics content, 1,1-diphenyl picrylhydrazyl free radical scavenging and total antioxidant potentials of seven indian medicinal plant parts’ aqueous extracts - SOUREN GOSWAMI; SANJIB RAY (International Journal of Pharma and Bio Sciences, 2017)
Here, relative total phenolics, 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging, total antioxidant potentials and phytochemical profiles of seven ethnomedicinally important, mostly antitumor, plant parts’ aqueous extracts (leaves of: Cordia dichotoma, Holoptelea integrifolia, Crinum asiaticum; aerial parts of: Croton bonplandianum, Cayratia carnosa, Scadoxus multiflorus and seeds of: Trigonella foenum-graecum) were analyzed. Data indicate the different extracts with varied amounts of phenolics and their differential capacity to neutralize the DPPH free radicals and total antioxidant activity. Out of the seven extracts, the maximum free radical scavenging, total antioxidant activity and the highest phenolics content was found in C. asiaticum. The preliminary phytochemical analysis indicates the prevalent secondary metabolites are alkaloids, terpenoids, tannins and saponins. In summary, considering the relative phenolics abundance and antioxidant activities, it can be concluded that out of seven anticancer plant products tested here C. asiaticum leaf aqueous extract possesses the highest efficient free radical scavengers and antioxidant potentials. Therefore, further study demands for in vivo antioxidant and cyto-genotoxic potentials of C. asiaticum.